Comparative study: 1Malaysia clinic and health clinics / Mustazimah Azelan … [et al.] - Azelan, Mustazimah; Gunggut, Haijon; Rosline, Abdul Kadir; Zaaba, Zuraidah (Faculty of Administrative Science and Policy Studies, 2012)
1Malaysia clinics and government health clinics are example of healthcare program available in Malaysia. Basically both clinics have almost the same functions and ideas of establishment but under different programs and name. Based on the review of previous literature done, there is very few research related to 1Malaysia clinics and no research that compared 1Malaysia clinics and health clinics had been found. This study is a preliminary research of 1Malaysia clinics. The objective is to compare 1Malaysia clinics with health clinics in terms of tangibles, reliability, responsiveness and accessibility. Through this study, enable assessment of the rationale for the 1Malaysia clinics establishment is able to be made. The study employed semi-structured interviews and observation. The interviewees involved department of health officer and both 1Malaysia clinic and conventional clinic staff and patients. Observation of both clinics were also made and the results indicated that 1Malaysia clinic provided better service in term of accessibility than health clinics. On the other hand, health clinics provided better service in tangibles, reliability and responsiveness. Overall, health clinics provide better service to customers. This is not surprising since 1Malaysia clinics would normally be upgraded to health clinics after achieving certain standard.